(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2013)
Fetus- in- fetu is a rare abnormality secondary to the abnormal embryogenesis in a diamniotic, monochorionic pregnancy. It is a rare pathological condition and fewer than 200 cases have been reported in the literature. We are reporting a case in which a 15 year old girl presented with a painful lump in left upper abdomen. Preoperative imaging, exploration and macroscopic examination of the excised specimen revealed it a case of fetus- in - fetu. This case is unique in terms of age of presentation and mature fetus like external appearance. DOI: http://dx.doi.org/10.3329/jpsb.v2i1.15162 Journal of Paediatric Surgeons of Bangladesh (2011) Vol. 2 (1): 36-39